CP-112 Beneficial effects of pharmaceutical follow-up in long-term geriatric units. (24th February 2014) - Palosse-Cantaloube, L; Di Fiore-Faye, C; Cyrus, A; Laborde, C; Lebaudy, C; Hermabessière, S; Gérard, S; Rolland, Y; Cestac, P
Abstract : Background: Improving the quality of medicines prescribing is one of the first steps to ensuring patient safety in hospital wards. Every day, in the geriatric department of Toulouse University Hospital, pharmacists analyse all new prescriptions. However, in long-term care units treatments are not always re-evaluated and this can lead to inappropriate prescribing or monitoring. Purpose: To detect and describe the prescribing errors in four long-term geriatric care units despite daily pharmaceutical analysis. Materials and methods: This study was conducted between January and August 2011 in 4 long-term geriatric care units of Toulouse University Hospital. Prescriptions were reviewed by three residents and two pharmacists. All interventions were proposed to three geriatricians for validation, recorded in an Excel spreadsheet and coded according to the criteria defined by the French Society of Clinical Pharmacy. The drug-related problems (=DRPs) and the most frequently involved drug classes were then described. Results: We reviewed the treatment of 135 inpatients: 64.4% women and 35.6% men. Mean age was 82.9 years old. We analysed 1492 lines of drugs and detected 471 potential drug-related problems (DRPs) in 125 inpatients. Drugs without indication represented 48% of DRPs, followed by improper administration (e.g. inappropriate route of administration) (18.5%), failure to receive drug (12%) and sub/supratherapeutic dosage (5%). Of all interventions, 298 (63.3%) were accepted and resulted in a modification of the prescription. The classes of drugs most involved in DRPs and pharmaceutical interventions were 'Nervous system' drugs (42%) and 'Alimentary tract and metabolism' drugs (22%). Conclusions: The high number of interventions accepted confirms that prescribing in long-term care units needed to be reviewed, despite daily pharmaceutical analysis. The major types of DRPs encountered, such as drugs without indication, reflect the lack of prescription update regarding the patients' current condition. This analysis underlines the importance of thoroughly and regularly re-evaluating medicines prescribing in long-term care units of hospital geriatric departments. No conflict of interest.